2014
DOI: 10.1017/s1355617714000356
|View full text |Cite
|
Sign up to set email alerts
|

APOE Moderates the Association between Lifestyle Activities and Cognitive Performance: Evidence of Genetic Plasticity in Aging

Abstract: The current study examined independent and interactive effects between Apolipoprotein E (APOE) genotype and two types of cognitively-stimulating lifestyle activities (CSLA)—integrated information processing (CSLA-II) and novel information processing (CSLA-NI)—on concurrent and longitudinal changes in cognition. Three-wave data across six years of follow-up from the Victoria Longitudinal Study (n = 278; ages 55–94) and linear mixed model analyses were used to characterize the effects of APOE genotype and partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Cognitive activities may be a way to maintain cognitive function in older adulthood, a principle summarized by the adage “use it or lose it” (Bielak, 2010; Hertzog et al, 2008; Hultsch et al, 1999). However, this effect may be moderated by biological or genetic risk factors (Runge, Small, McFall, & Dixon, 2014). “Use it or lose it” is a principle of experience-dependent brain plasticity such that synaptic connections that are not sufficiently engaged will weaken and be lost over time (Kleim & Jones, 2008).…”
mentioning
confidence: 99%
“…Cognitive activities may be a way to maintain cognitive function in older adulthood, a principle summarized by the adage “use it or lose it” (Bielak, 2010; Hertzog et al, 2008; Hultsch et al, 1999). However, this effect may be moderated by biological or genetic risk factors (Runge, Small, McFall, & Dixon, 2014). “Use it or lose it” is a principle of experience-dependent brain plasticity such that synaptic connections that are not sufficiently engaged will weaken and be lost over time (Kleim & Jones, 2008).…”
mentioning
confidence: 99%
“…Previous reports have shown that neuroticism levels discriminate between healthy aging and early‐stage AD (Duchek et al ., ), and an active lifestyle may act as a buffer against the negative effects of high neuroticism in at‐risk adults (Wang et al ., ). The present sample may have benefited from both healthy aging, with lower neuroticism levels, and a relatively advantaged socially engaged lifestyle (Runge et al ., ). Whether lifestyle activities play a specific role in this gene–personality dynamic should be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic association studies have been useful in identifying the degree of risk associated with some alleles in selected SNPs for cognitive changes with aging (Kremen and Lyons, 2011). However, for many neurocognitive phenotypes, the consideration of personal attributes and lifestyle activities may supplement or modify the observed roles of biological (genetic) factors (Runge et al, 2014;Sachs-Ericsson et al, 2010;Shanahan and Hofer, 2005). Personality traits encompass a wide range of behaviors as typically summarized in a specific set of dimensions or patterns characteristic to given individuals, and they are generally stable in adulthood (Soubelet and Salthouse, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, APOE allelic variation has been assumed to relate to plastic responses to cognitive training interventions. Although results are inconclusive, it has been suggested that ε4 carriers may show less cognitive plasticity than non-carriers (Feng et al, 2015;Polito et al, 2015;Runge, Small, McFall, & Dixon, 2014;Zehnder et al, 2009). As the prevalence of people living with dementia is increasing (Livingston et al, 2017), it is of interest to study whether genetic variation, IQ, and modifiable lifestyle factors impact memory plasticity in a controlled experimental intervention.…”
Section: Introductionmentioning
confidence: 99%